Utilizing the YouTube Platform to Familiarize Students with Mathematical Literacy in Elementary Schools - Wathoni, Lalu Nurul (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2025)
The aim of this research is to familiarize elementary school students with mathematical literacy in utilizing digital media, one of which is the YouTube platform. Literacy here means reading and writing symbols, numbers and understanding how to solve basic mathematical problems. The research method uses qualitative research with a qualitative descriptive approach, namely an approach that aims to understand phenomena in depth in a natural context. Primary data was obtained directly through interviews, observation and documentation of the main informants consisting of the Principal (1 person), Class Teacher (1 person), and 25 class V students of Al Masyhuriah Islamic Elementary School, Kateng Village (16 male students and 8 female students). Data analysis was carried out in three stages, namely: (1) Data reduction; (2) Presentation of data; and (3) Drawing conclusions. Based on research results, it has been shown that the use of the YouTube platform can help familiarize students with mathematical literacy in the affective, cognitive and psychomotor domains. This research has the limitation that students' mathematical literacy habits are influenced by their ability to use and utilize YouTube as a learning resource and source of information. This research also cannot be generalized to the entire student population, because it was conducted on a selected sample group.